THE IMPORTANCE OF MEASUREMENT SYSTEMS IN ENHANCING ACCURACY IN WELDING (Web of Technology: Multidimensional Research Journal, 2024)
Welding is a critical process in manufacturing, where accuracy directly affects the quality and reliability of the final product. Measurement systems play a vital role in maintaining precision by monitoring parameters such as joint geometry, heat input, and material deformation. This study examines how integrating advanced measurement technologies can improve welding accuracy, reduce defects, and enhance overall production efficiency.